Inorganic Polyphosphate Interacts with Nucleolar and Glycosomal Proteins in Trypanosomatids - Negreiros, Raquel S. (Mol Microbiol, 2018)
Inorganic polyphosphate (polyP) is a polymer of three to hundreds of phosphate units bound by high-energy phosphoanhydride bonds and present from bacteria to humans. Most polyP in trypanosomatids is concentrated in acidocalcisomes, acidic calcium stores that possess a number of pumps, exchangers, and channels, and are important for their survival. In this work, using polyP as bait we identified > 25 putative protein targets in cell lysates of both Trypanosoma cruzi and T. brucei. Gene ontology analysis of the binding partners found a significant over-representation of nucleolar and glycosomal proteins. Using the polyphosphate-binding domain (PPBD) of Escherichia coli exopolyphosphatase we localized long chain polyP to the nucleoli and glycosomes of trypanosomes. A competitive assay based on the pre-incubation of PPBD with exogenous polyP and subsequent immunofluorescence assay of procyclic forms of T. brucei showed polyP concentration-dependent and chain length-dependent decrease in the fluorescence signal. Subcellular fractionation experiments confirmed the presence of polyP in glycosomes of T. brucei procyclic forms (PCF). Targeting of yeast exopolyphosphatase to the glycosomes of PCF resulted in polyphosphate hydrolysis, alteration in their glycolytic flux and increase in their susceptibility to oxidative stress.